PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI DESA LUKBAYUR KECAMATAN TANTA KABUPATEN TABALONG ( INFRASTRUKTUR JALAN USAHA TANI (JAPB, 2022)
Community participation is needed in determining policies and decisions and is often discussed in various areas, both in urban and rural areas because we can see that the influence of this participation is so great, this community participation determines a plan or programs that are around them, the success of a program without the existence of community participation will not run well, community participation will be needed in planning or programs, so that programs run as they should. The purpose of this study was to find out and analyze how community participation in the infrastructure development of Lukbayur Village, Tanta District, Tabalong Regency. The method used in this research is a qualitative research approach with descriptive research type. The technique used in conducting research or data collection is by using a questionnaire, observation and documentation. In this study, for the purposes of data analysis, the authors did not use statistical analysis techniques in the sense that they were not related to scores and scales. Instead, they only used simple statistical analysis techniques with percentages (%) and then the data obtained from the respondents were analyzed or processed to become descriptive qualitative. The results of this study indicate that the participation of the people of Lukbayur Village, Tanta District, Tabalong Regency in development, especially the construction of farming roads in Lukbayur Village, Tanta District, Tabalong Regency has not been satisfactory and cannot be categorized (66.72%), this is because community work and education level are factors obstacles in the development of farm road infrastructure. Keywords: Participation, Development, Road Infrastructure.